My Sports Field Programme – Orlik 2012 as a Factor of Local Development - Jakub Gradziuk (Barometr Regionalny, 2015)
The study is devoted to the characteristics of the implementation of My Sports Field Programme – Orlik 2012 (in Polish: Moje Boisko Orlik-2012) in the years 2008–2011, based on the examples of chosen communes from hrubieszowski, tomaszowski and zamojski counties, located in Lubelskie Voivodship. The main aim of the article was to identify the role Orlik sports fields play in the socio-economic development of a commune in the market economy. Thus an analysis was carried out of the functioning of existing and planned investments in the project as well as research in selected local government units not benefiting from the programme.